Myosteatosis Differentially Affects the Prognosis of Non-Metastatic Colon and Rectal Cancer Patients: An Exploratory Study - Pozzuto, Lara; Silveira, Marina Nogueira; Mendes, Maria Carolina Santos; Macedo, Lígia Traldi; Costa, Felipe Osório; Martinez, Carlos Augusto Real; Coy, Cláudio Saddy Rodrigues; da Cunha Júnior, Ademar Dantas; Carvalheira, José Barreto Campello (Frontiers in Oncology, 2021)
Body composition performed by computed tomography (CT) impacts on cancer patients’ prognoses and responses to treatment. Myosteatosis has been related to overall survival (OS) and disease-specific survival in colorectal cancer (CRC); however, the independent impact of the association of myosteatosis with prognosis in colon cancer (CC) and rectal cancer (RC) is still unclear. CT was performed at the L3 level to assess body composition features in 227 patients with CRC. Clinical parameters were collected. Overall survival (OS) was the primary outcome, and the secondary outcome was disease-free survival (DFS). Skeletal muscle attenuation and intramuscular adipose tissue area were associated with DFS (P = 0.003 and P = 0.011, respectively) and OS (P < 0.001 and P < 0.001, respectively) in CC patients but not in RC patients. Only skeletal muscle area was associated with better prognosis related to OS in RC patients (P = 0.009). When CC and RC were analyzed separately, myosteatosis influenced survival negatively in CC patients, worsening DFS survival (hazard ratio [HR], 2.70; 95% confidence interval [CI], 1.07–6.82; P=0.035)and OS (HR, 5.76; 95% CI, 1.31–25.40; P=0.021). By contrast, the presence of myosteatosis did not influence DFS (HR, 1.02; 95% CI, 0.52–2.03; P=0.944) or OS (HR, 0.76; 95% CI, 0.33–1.77; P=0.529) in RC patients. Our study revealed the interference of myosteatosis in the therapy and survival of patients with CC but not of those with RC, strengthening the value of grouping the two types of cancer in body composition analyses.